Intention of use of contraceptive methods among puerperal women of a university hospital - Bibiane Dias Miranda Parreira; Sueli Riul da Silva; Mário Alfredo Silveira Miranzi (Rev Rene)
This quantitative study was carried out with 358 puerperal women interned in a university hospital of Uberaba — MG, for three months. Its aim was to describe the intention of puerperal women regarding the use and type of contraceptive methods after birth, place of acquisition and source of orientation of such contraceptives. The data were obtained by means of a structured instrument and analyzed by descriptive statistics. 340 (98,8%) of the participants wanted to use a contraceptive method after birth. The main methods they wished to use were: oral contraceptive, hormonal injection and tubal ligation. The most mentioned place for acquisition of contraceptives was the drugstore. The main source of orientation mentioned was the physician. Most of the puerperal women intended to use a contraceptive method after birth, a crucial fact for the fulfillment of their reproductive planning. They should have guaranteed access to contraceptive methods in health services, as well as to receive the guidelines from various health professionals.